Charge injection characteristics of sputtered ruthenium oxide electrodes for neural stimulation and recording. Issue 1 (14th July 2021) - Chakraborty, Bitan; Joshi‐Imre, Alexandra; Cogan, Stuart F.
Abstract: We have studied the charge‐injection characteristics and electrochemical impedance of sputtered ruthenium oxide (RuOx ) films as electrode coatings for neural stimulation and recording electrodes. RuOx films were deposited by reactive DC magnetron sputtering, using a combination of water vapor and oxygen gas as reactive plasma constituents. The cathodal charge storage capacity of planar RuOx electrodes was found to be 54.6 ± 9.5 mC/cm 2 (mean ± SD, n = 12), and the charge‐injection capacity in a 0.2‐ms cathodal current pulse was found to be 7.1 ± 0.3 mC/cm 2 (mean ± SD, n = 15) at 0.6 V positive bias versus Ag|AgCl, in phosphate buffer saline at room temperature for 250 nm thick films. In general, the RuOx films exhibited high charge‐injection capacities, with or without a positive interpulse bias, comparable to sputtered iridium oxide (SIROF) coatings. The charge‐injection capacity increased monotonically with film thickness from 120 to 630 nm, and reached 11.30 ± 0.34 mC/cm 2 (mean ± SD, n = 5) at 0.6 V bias versus Ag|AgCl at 630 nm film thickness. In addition, RuOx films showed minimal changes in electrochemical characteristics over 1.5 billion cycles of constant current pulsing at a charge density of 408 μC/cm 2 (8 nC/phase, 200 μs pulse width). The findings of low‐impedance, high charge‐injection capacity, and long‐term pulsing stability suggest the suitability of RuOx as a comparatively inexpensive and favorable choice of electrode material for neural stimulation and recording.